Image Processing and Communications Challenges 7 - Choraś, Ryszard S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book contains papers accepted for IP&C 2015, the International Conference on Image Processing and Communications, held at UTP University of Science and Technology, Bydgoszcz, Poland, September 9-11, 2015. This conference was the eighth edition in the IP&C series of annual conferences. This book and the conference have the aim to bring together researchers and scientists in the broad fields of image processing and communications, addressing recent advances in theory, methodology and applications. The book will be of interest to a large group of researchers, engineers and practitioners in image processing and communications.
Keywords: Computational intelligence; Artificial intelligence; Signal processing; Telecommunication; Computational Intelligence; Artificial Intelligence; Signal, Speech and Image Processing; Communications Engineering, Networks